Wymóg świeckiego uzasadnienia w dyskursie publicznym a wolność religijna - Mirocha, Łukasz (PRAWO i WIĘŹ, 2025)
The paper addresses the issue of the compatibility of the requirement to use secular justifications in public discourse with the principle of religious freedom. The first part of the paper outlines the basic assumptions of exclusivism – the position that advocates abandoning religious argumentation in the public sphere. It presents the philosophical justifications for this requirement, the forms it takes, and the objections raised against the doctrine of exclusivism. The second part of the paper discusses the provisions of the European Convention on Human Rights regarding religious freedom and freedom of expression. The next part analyses the problem referred to in the title. The paper notes the risk of the instrumentalisation of religious argumentation and the related inability to recognise that this type of rationalisation is protected by religious freedom. It also emphasises that the scope of protection may depend on the content of religious argumentation and other factors.